In-situ quantification of intra and intergranular deformation in pure magnesium using full-field measurements at low and high strain rates. (November 2018) - Malchow, Peter; Koohbor, Behrad; Ravindran, Suraj; Kidane, Addis
Highlights: Global material response was found to be dependent on initial grain orientation. Contribution of intergranular to intragranular deformation was large in cast Mg. Strain rate sensitivity was related to the amount of grain boundary deformation. Abstract: Due to the presence of weak grain boundaries as well as significantly coarse grain structure with minimal deformability, grain boundary cracking is almost an inevitable source of failure when a cast magnesium-based alloy is deformed at low homologous temperatures. The main objective in this work is to quantitatively investigate the contribution of inter- and intragranular deformation to the macroscale deformability and ductility of nominally pure as-cast magnesium subjected to quasi-static and dynamic loading. The proposed mesoscale full-field measurement approach is first presented and verified through measurements carried out to investigate deformation and grain boundary cracking in cast magnesium subjected to quasi-static loading. The method is then extended into the analysis of mesoscale deformation and failure under dynamic loading conditions using an experimental setup consisting of a split Hopkinson pressure bar (SHPB) and a high-speed imaging system. In both cases, the effect of the initial grain configuration on the local deformation response of Mg is investigated. The results indicate that the contribution of grain boundary region deformation to the total deformation exerted on the Mg samples is significant and depends on the initial grain configuration. Also, the strain rate sensitivity of the material is found to be dominated by the material deformation in the vicinity of grain boundaries.